Teologia desde a América Latina: interpretação das fissuras históricas com pretensão de verdade, em diálogo com Theodor W. Adorno - Junges, Fábio César (2015)
Latin American theology has its history and its place in history. Its basic notions are founded on the interpretation of reality from the perspective of the cross. Presently it is in need of being resumed and actualized, especially in the light of recent hermeneutical debates. Our proposal here is that this be done from the point of view of specific contribution of Theodor Adorno to these debates. Adorno is normally ot considered a hermeneutical philosopher. He does not name his philosophy hermeneutic ; but he would insist that his is an interpretative philosophy. His project is certainly not devoid of hermeneutical elements. It is our contention that it has a significant contribution to Latin American Theology in its quest for present relevance. Adorno's philosophy can help to understand that the text to be interpreted does not hold any absolute truth. The text is anything but unconcluded, broken, paradoxical, open to blind demons . The texts that try to capture it must be an interpretation of a damaged reality, with no light and no hope, in a no hope environment. This means, first, to maintain the interpretative character from a perspective of suspicion, with the expectation to, second, get to a thought of right and justice, guided by the perspective of the victims of history. Theology from Latin America is, in this case, negative and reverse, from its very opposite, from the victims, the demoted and condemned. If there is some positivity, it will appear under a sign of total negativity, preserved only on the negation act. This thinking act needs a really true asceticism, so that the temptation of positive words may be resisted, in line with the words about Jesus in Luke 2, 34: a sign of contradiction . Theology from Latin America is a sign of contradiction emerging from the the shadow of the Cross, from the darkness of the sixth to the ninth hour. Jesus' cross is also theology's cross. Any possible light in theology shall have the form of sparks through the cross's darkness. The desperation of the Cross's scandal, taken to completeness, may turn in it's opposite. This is the only hope for theology as genuine interpretative theology, with no hold on claims of absolute truth, with no secure hermeneutical key.